2020
DOI: 10.22271/chemi.2020.v8.i3h.9285
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sulphur and zinc fertilization on productivity and economics of sesame (Sesamum indicum L.) in semi-arid conditions of Rajasthan

Abstract: A field experiment was conducted at Agronomy farm, S.K.N. College of Agriculture, Jobner, Jaipur (Rajasthan) during kharif season of 2018 to study the effect of sulphur and zinc fertilization on productivity and economics of sesame. The experiment comprising of four levels each of sulphur (0, 15, 30 and 45 kg/ha) and zinc (0, 10, 20 and 30 kg zinc sulphate/ha), thereby making 16 treatment combinations was laid out in factorial randomized block design and replicated thrice. Results showed that progressive incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…two hand weeding and hoeing in sesame significantly gave higher seed yield than rest of the integrated weed management practices". Among the different herbicidal treatments, the lowest weed density of 37/m 2 and dry weight 126 g/m 2 were recorded by preemergence application of Pendimethalin 30 EC @ 0.50 kg a.i./ha + Hand weeding at 20 DAS followed by pre-emergence application of Pendimethalin 30 EC @ 0.50 kg a.i./ha (R) + Post-emergence application Quizalofop-ethyl 50 g a.i./ha at 20 DAS.These results are in conformity with the findings of Yadav S.S. [10]. The maximum weed index of 68.33 % was recorded in weedy check plots (T 1 ) which gradually reduced due to the different herbicidal treatments and became minimum (16.33%) in T 6 [Pendimethalin 30 EC (Pre-emergence) @ 0.50 kg a.i./ha + Hand weeding at 20 DAS] followed by 20.67 % in T 8 [Pendimethalin 30 EC (Preemergence) @ 0.50 kg a.i./ha + Sodium Acifluorfen 16.5% + Clodinafop-Propargyl 8% EC (premix) @ 100 g a.i/ha at 20 DAS].…”
Section: Effect On Weedssupporting
confidence: 90%
“…two hand weeding and hoeing in sesame significantly gave higher seed yield than rest of the integrated weed management practices". Among the different herbicidal treatments, the lowest weed density of 37/m 2 and dry weight 126 g/m 2 were recorded by preemergence application of Pendimethalin 30 EC @ 0.50 kg a.i./ha + Hand weeding at 20 DAS followed by pre-emergence application of Pendimethalin 30 EC @ 0.50 kg a.i./ha (R) + Post-emergence application Quizalofop-ethyl 50 g a.i./ha at 20 DAS.These results are in conformity with the findings of Yadav S.S. [10]. The maximum weed index of 68.33 % was recorded in weedy check plots (T 1 ) which gradually reduced due to the different herbicidal treatments and became minimum (16.33%) in T 6 [Pendimethalin 30 EC (Pre-emergence) @ 0.50 kg a.i./ha + Hand weeding at 20 DAS] followed by 20.67 % in T 8 [Pendimethalin 30 EC (Preemergence) @ 0.50 kg a.i./ha + Sodium Acifluorfen 16.5% + Clodinafop-Propargyl 8% EC (premix) @ 100 g a.i/ha at 20 DAS].…”
Section: Effect On Weedssupporting
confidence: 90%
“…Consequently, this led to an elevated photosynthetic rate, facilitating greater production and translocation of photo assimilates to the onion bulbs. Yadav et al [48] observed a similar phenomenon, where a balanced nutrient application promoted vegetative growth and chlorophyll synthesis, ultimately enhancing assimilate production and bulb yield in onions. Similarly, Assefa et al [38] found that applying NPS fertilizer at a rate of 130 : 20 : 21 and Zn at 15 kg/ha resulted in the highest bulb yield (25.38 t/ha), while the lowest yield (9.81 t/ha) occurred with 0 : 0:0 kg/ha NPS and 0 kg/ha Zn.…”
Section: Total Bulb Yieldmentioning
confidence: 82%
“…The synergistic effect of sulphur application in increasing productivity of sesame, (Chanda 2003). The sulphur, zinc and boron combinedly results in nutrient balance, important in photosynthesis process which directly bearing on plant growth and development [24]. The application of micronutrients cause improvement in soil-physical chemical properties and nutrient availability to crop during vegetative growth, (Sankaran 2001).…”
Section: Yield Attributes and Yieldmentioning
confidence: 99%